Pola Konsumsi Makanan Satwika Pada Bhakta Hare Krishna di Sri Sri Krishna Balarama Ashram Denpasar - I Gede Sutana (Satya Widya: Jurnal Studi Agama, 2020)
Food is a means of survival. In terms of food, humans have each associated with food consumption patterns. In this research, what is interesting is that Bhakta Hare Krishna in Sri Sri Krishna Balarama Ashram Denpasar has a different food consumption pattern than the general public. Bhakta Hare Krishna in Sri Sri Krishna Balarama Ashram Denpasar does not provide food containing meat, fish, and eggs. This food consumption pattern is called the satwika food consumption pattern. About the observations in this paper related to the pattern of consumption of satwika food at Bhakta Hare Krishna in Sri Sri Krishna Balarama Ashram Denpasar.In further observation of functional choice theory and structural functionalism became a knife of analysis to reveal patterns of consumption of satwika food at Bhakta Hare Krishna at Sri Sri Krishna Balarama Denpasar Ashram. Bhakta Hare Krishna applies the pattern of consumption of satwika food based on the applicable provisions, rational choice of devotees, and functional for life both physical and spiritual life. Satwika food consumption patterns indicate five agreed components (1) how to obtain satwika food ingredients, (2) types of satwika food ingredients, (3) satwika food menu, (4) how to process satwika food, and (5) how to serve satwika food. As well as the implications obtained from the application of the satwika food consumption patterns have physical, mental and spiritual implications. Keywords: Satwika Food Consumption Pattern, Bhakta Hare Krishna, Sri Sri Krishna Balarama Ashram Denpasar